Assessing the Rules of Functioning and Organization of the Wholesale Natural Gas Market in the European Union and Ukraine: Legal and Socio-political Perspective: Part I: The Backdrop: Natural Gas Market in the EU and Ukraine - Kosiński, Eryk; Mikulska, Anna (PRAWO i WIĘŹ, 2021)
This author considers current European Union and Ukraine’s wholesale natural gas market in light of regulatory measures that had been enacted and/or implemented with respect to its organization and functioning. The analysis points to three major goals EU’s energy sector regulation is geared to achieve: 1) economic (i.e. procompetitive support); 2) energy security; and 3) social goals. As such, the EU wholesale energy market can be regarded as a regulatory instrument. Ukraine assumed the obligation to implement EU legislation in the field of energy sector regulation (Energy Community acquis communautaire): Act of Ukraine No. 329-VIII of 9 April 2015 on natural gas market implements fundamental principles of the third energy package in the area of organization and functioning of the wholesale natural gas market. However, for Ukraine’s wholesale energy market to assume characteristics of a regulatory instrument akin to the EU market, further implementation of EU regulation 1227/2011 (REMIT) and, to some extent, implementation of the fourth energy package is needed. In the Part 1 author focuses on providing a background on gas market conditions in the EU and Ukraine, which will provide an important backdrop for the second part of this study where he will discuss in specific regulatory issues associated with adoption of EU gas market principles in the Ukrainian gas market.